Community-led participatory approaches to improving dietary diversity in Vihiga County, Kenya - Nowicki, Marisa; Aluso, Lilian; Termote, Céline (2020)
An information sheet with brief overview of the Alliance of Bioversity International and CIAT and the work that has been carried out in Vihiga County since 2015. The information sheet briefly presents the results of the quasi-experimental evaluation exercise of the integrated community based approach for farm market and diet diversity that was developed and first tested in Vihiga County and published in Boedecker et al. 2019 (Participatory farm diversification and nutrition education increase dietary diversity in Western Kenya. Maternal and Child Nutrition, 15(3): e12803) The information sheet further explains the next steps that were taken such as guiding the same communities to set up their own farmer resource centres and community seed bank for traditional leafy vegetables. The information sheet was used to engage policy makers in the next step of the project that is meant to scale up and out different aspects of the project together with Vihiga County policy makers and other stakeholders.